PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS DENGAN EFEKTIVITAS KOMITE AUDIT SEBAGAI VARIABEL MODERASI TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021–2025 - Jihan Safhira Sani; Tapi Rumondang Sari Siregar; Muhammad Rizal; Khairunnisa Harahap; Muhammad Ridha Habibi Z (UNHI Press, 2026)
This study aims to examine the effect of firm size and profitability on audit report lag with audit committee effectiveness as a moderating variable in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. This study employed a quantitative approach using secondary data obtained from annual reports and audited financial statements. The sample was selected using purposive sampling, resulting in 21 healthcare companies with 101 observations. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that firm size has no significant effect on audit report lag, whereas profitability has a significant negative effect on audit report lag. Furthermore, audit committee effectiveness is unable to moderate the relationship between firm size and audit report lag but strengthens the negative relationship between profitability and audit report lag. These findings suggest that effective audit committee monitoring contributes to improving the timeliness of audited financial reporting, particularly in highly profitable healthcare companies, thereby enhancing the efficiency of the audit completion process.